2014
DOI: 10.1155/2014/642942
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamon: A Multifaceted Medicinal Plant

Abstract: Cinnamon (Cinnamomum zeylanicum, and Cinnamon cassia), the eternal tree of tropical medicine, belongs to the Lauraceae family. Cinnamon is one of the most important spices used daily by people all over the world. Cinnamon primarily contains vital oils and other derivatives, such as cinnamaldehyde, cinnamic acid, and cinnamate. In addition to being an antioxidant, anti-inflammatory, antidiabetic, antimicrobial, anticancer, lipid-lowering, and cardiovascular-disease-lowering compound, cinnamon has also been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
332
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 557 publications
(414 citation statements)
references
References 120 publications
10
332
0
11
Order By: Relevance
“…It can be clearly seen that cinnamaldehyde was the major components in both Soxhlet and water extract which contributed to 74.14% and 71.69% of total constituents, respectively. This result is parallel with many previous studies [6,7,[12][13][14]. These studies showed that cinnamaldehyde is the major component in C. zeylanicum which contribute from 60% to 80% of total components.…”
Section: Gas Chromatography/ Mass Spectrometry (Gcms) Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…It can be clearly seen that cinnamaldehyde was the major components in both Soxhlet and water extract which contributed to 74.14% and 71.69% of total constituents, respectively. This result is parallel with many previous studies [6,7,[12][13][14]. These studies showed that cinnamaldehyde is the major component in C. zeylanicum which contribute from 60% to 80% of total components.…”
Section: Gas Chromatography/ Mass Spectrometry (Gcms) Analysissupporting
confidence: 91%
“…Cinnamon can be considered as one of the oldest herbal medicine since it has been mentioned in Chinese texts for over 4000 years ago [6]. They cited the traditional uses of cinnamon which are as flavoring agent, insecticidal, antifungal and also as a treatment of dental problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been published on this topic. [61,[153][154][155][156][157][158] Some systematic reviews and metaanalyses concluded that cinnamon has a beneficial effect on glycemic control. [58,142,[159][160][161][162] Due to its nutraceutical potential, Viuda-Martos and his coworkers suggested that the spice can be considered essential components of our diet.…”
Section: Research Gaps and Future Prospectsmentioning
confidence: 99%
“…Numerous reports have distributed with the numerous attributes of cinnamon in the forms of, essential oils, bark, bark powder, flavonoids, phenolic compounds, and isolated constituents. Each of these attributes plays a vital role in the improvement of persons health (53). In fact, Akilen et al found that the regimen of cinnamon decreased both systolic and diastolic BP in T2DM from 132.6 to 129.2 mm Hg and 85.2 to 80.2 mm Hg, one-toone (45).…”
Section: Discussionmentioning
confidence: 99%